Household Solid Fuel Use and Associated Factors in Ethiopia: A Multilevel Analysis of Data From 2016 Ethiopian Demographic and Health Survey - Mastewal Endalew; Daniel Gashaneh Belay; Nuhamin Tesfa Tsega; Fantu Mamo Aragaw; Moges Gashaw; Melaku Hunie Asratie (SAGE Publishing, 2022)
Solid fuels are types of fuel that comprise coal, biomass, charcoal, wood, or straw and are used for cooking, heating, lighting, boiling water, and generating revenue at home. Globally, 3 billion of the world's poorest people continue to rely on inefficient solid fuels, which produce health-damaging contaminants. In Ethiopia, more than 90% of households rely on wood as their primary source of energy. The actual and potential determinants of solid fuel use have not been fully identified, particularly at the national level in Ethiopia. Therefore, this study aimed to determine the magnitude of solid fuel use and its associated factors in Ethiopia. We used the Ethiopian Demographic and Health Survey (EDHS), which was conducted in 2016. The data was conducted using a 2-stage stratified cluster sampling approach. A total of 16 650 weighted samples were taken. Multilevel logistic regression models were fitted to identify factors associated with solid fuel use, and a cluster-level random intercept was introduced in the mixed model. An adjusted odds ratio with a 95% confidence level was reported to show the strength of the association and its significance. The goodness of fit of the model was checked using proportional change deviance (PCV). The magnitude of solid fuel use among households in Ethiopia was 94.03% (95% CI = 93.66, 94.37). Household heads completed in primary school (AOR, 3.09, 95% CI = 2.44, 3.91), outdoor cooking places (AOR, 4.13, 95% CI = 2.96, 5.76), and small peripheral regions (AOR, 14.44, 95% CI = 6.12, 34.04) were all significantly associated with solid fuel use. The intra-cluster correlation coefficient (ICC) showed that about 81% of the variations in the use of solid fuel were attributed to the difference at the 643 cluster level, but the remaining 19% were attributed to individual household factors. The PCV was 90%, which showed that the variation in solid fuel use among study households was explained by factors at both the individual and community levels. The deviation test of the fourth model had the lowest value (3528) and was chosen as the best-fitted model. Due to different influencing factors, the use of solid fuel is still high in Ethiopia. Promoting access to education and raising awareness toward solid fuel impact is very important.